1993
DOI: 10.1007/bf01446994
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation after lumbar disc surgery: Results in 130 cases

Abstract: Out of a series of 1850 cases operated upon for lumbar disc herniation 130 underwent re-operation because of persistent or recurrent symptoms. Re-operation was successful in 62%. The prognosis of re-operation was not related to special clinical symptoms and signs but only to the operative findings. Herniations at other levels and recurrences of lumbar disc herniations had the best results (excellent in 98% respectively 54%), but scar formations alone came out much less satisfactory (only 38% excellent results)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 17 publications
1
77
1
16
Order By: Relevance
“…15 A recurrence rate of 5% to 15% for LDH has been reported. [1][2][3][4][5] Differentiation of recurrent disc herniation from scar formation will allow for improved treatment choices and selection of patients who may benefit from a second surgery. Gadoliniumenhanced MRI is thought to be the best modality to differentiate between these two diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A recurrence rate of 5% to 15% for LDH has been reported. [1][2][3][4][5] Differentiation of recurrent disc herniation from scar formation will allow for improved treatment choices and selection of patients who may benefit from a second surgery. Gadoliniumenhanced MRI is thought to be the best modality to differentiate between these two diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] There have been many studies designed to determine the recurrence of LDH, and various risk factors suggested including disc degeneration, trauma, age, smoking, gender, and obesity. 1,3,6 Radiologically identifiable factors, such as disc degeneration, disc height, and sagittal range of motion have been shown to be related to spinal instability and consequently to rLDH.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent lumbar disc herniation (RLDH) is a major cause of surgical failure, the incidence of which is reported from 5 to 11%, with an increased incidence as the follow-up period is extended [2,5,13]. The optimal technique for treating RLDH is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Literature contains different views on definition of recurrent DH. Recurrent DH is expressed as the development of DH, on the same level, same part, or on the opposite part (13,14,15). Some other researchers defined different-level herniation as recurrent DH (16).…”
Section: Resultsmentioning
confidence: 99%